CONFLICT VARIABLES AS CORRELATES OF PUBLIC SECONDARY SCHOOL TEACHERS’ PRODUCTIVITY IN ADAMAWA STATE, NIGERIA (2013)
There has been persistent public concern on declining teachers’ productivity in public schools in Nigeria. This is partly attributable to poor working conditions, poor remuneration and conflict dynamics. Previous studies have explored the issues of working conditions and remuneration, while there has been a dearth of studies on the relative and composite impacts of conflict dynamics on teachers’ productivity in secondary schools in Adamawa State. This study, therefore, investigated the relationship between conflict variables and teachers’ productivity in public secondary schools in Adamawa State, Nigeria. The descriptive survey research design of the ex-post-facto was adopted. The multi-stage sampling procedure was used to select 1,528 teachers and 76 principals across public secondary schools in Adamawa State. In addition, purposive sampling technique was used to select five officials of Adamawa State School Board and three executive members of Nigeria Union of Teachers (NUT) and in-depth interview (IDI) was used to gather information from them. Conflict Variables and Teachers’ Productivity Scale (r = 0.89) was used to gather data. Eight research questions were answered and eight hypotheses were tested at 0.05 level of significance. Quantitative data were analysed using mean, Pearson Product Correlation Coefficient and Multiple Regression, while qualitative data were content analysed. Conflict variables jointly significantly correlated with teachers productivity = 71.14; R = 0.44, R2 = 0.41, Adj. R2 = 0.19; p < 0.05); accounting for 41% of the variance in the dependent variable. Their relative contributions were ranked as follows: conflict communication (ß = 0.40, p < 0.05); conflict management styles (ß = 0.16, p < 0.05); conflict level (ß = -0.16, p < 0.05); and conflict incident (ß = -0.06, p < 0.05). Significant relationship existed between each of the conflict management styles and teachers productivity as follows: collaborating (r = 0.32; p < 0.05); compromising (r = 0.10; p < 0.05) and accommodating (r = 0.07; p < 0.05). Competing and avoiding styles were not significant. The conflict management styles utilised by teachers are ranked in this order: collaborating ( =3.1); competing ( =2.55); accommodating ( =2.47); compromising ( =2.42); and avoiding ( =2.35). The conflict management styles highly preferred by principals are arranged as follows: collaborating ( =3.33); compromising ( =2.41); accommodating ( =2.29); avoiding ( =2.23); and competing ( =1.94). The IDI revealed that the School Board officials preferred avoidance style because of the pervading syndrome of godfatherism that often underscores teachers’ appointment. In addition, they indicated that conflict, when mismanaged, adversely affects teachers’ productivity. The NUT executive members opined that conflicts confronting teachers stem from poor management attitudes of principals and the School Board patterns of handling issues relating to promotion and salaries. Conflict variables are potent determinants of teachers’ productivity in public secondary schools. Therefore, teachers should be adequately exposed to conflict dynamics and its management patterns so as to make them more proactive in handling conflict for better performance in schools.